Trajectory modeling of modern dust transport to the Southern Ocean and Antarctica. Issue 18 (23rd September 2015) - Neff, Peter D.; Bertler, Nancy A. N.
Abstract: Aerosol deposition over the Southern Ocean and Antarctica has the potential to alter marine productivity and thus ocean carbon uptake while also impacting radiative balance due to scattering and absorption from atmospheric particulates. Quantification of modern emission, transport, and deposition of terrestrial dust and other airborne material from Southern Hemisphere sources is challenging due to low emission levels and poor detection from remote sensing platforms. Here forward trajectory modeling is used to explore atmospheric transport, independent of deposition processes, from 1979 to 2013. Trajectories are initiated from known arid dust source areas in South America (Patagonia), Australia, and southern Africa, with detailed consideration of New Zealand as a potential source. Results suggest that Patagonian and New Zealand dust and other aerosol emissions share strong atmospheric transport during all seasons, allowing even potentially small New Zealand emissions to contribute significantly to Southern Ocean and Antarctic aerosol loading. We find that atmospheric transport controlling distribution of dust and other aerosols shows distinct spatial variability. New Zealand and Patagonia rapidly contribute a high proportion of trajectories to West Antarctica, while in interior East Antarctica, source contributions are limited and highly mixed. The sensitivity of existing deep ice core sites to modern atmospheric transport is discussed. Finally, interannual variability of poleward trajectory extension over the Pacific and Atlantic sectors of the Southern Ocean highlights the association of both tropical Pacific sea‐surface temperature and high‐latitude wind variability (e.g., the Southern Annular Mode) with transport of dust and other aerosols to the Southern Ocean and Antarctica. Key Points: Dust transport is modeled using 35 years of daily forward trajectories Strongest transport to southern high latitudes is from Patagonia and New Zealand Southward transport modified by both low‐ and high‐latitude climate variability